The Consumer Perception Toward Product Quality And Price Of Indihome - Hardiansah, Wahyu; Hidayati, Nurul (STIE PGRI Dewantara Jombang, 2020)
This study aims to determine and identify the effect of product quality and price on the decision to use Indihome by PT Telekomunikasi Indonesia (Telkom). This type of research was quantitative. The population in this study were Indihome consumers in Jombang district, and a sample of 86 people. Data analysis using multiple linear regression method and hypothesis testing and coefficient of termination. Based on the research results indicate that the product quality and price of Indihome influence consumer decisions to buy these products.